Hubungan Teknik Tarik Benang Terhadap Perkembangan Motorik Halus Anak Usia Dini Kelompok A di Tk Beringin Permai Perumnas Pagar Beringin - Rumanthy Elisabeth Lumbantobing; Uranus Zamili; Endang Junita Sinaga (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Lumbantobing, Rumanthy. 2023. "The Relationship between the Thread Pulling Technique and the Fine Motor Development of Early Childhood Group A at the Beringin Permai Kindergarten Perumnas Fence Banyan". The aim of this research was to determine the relationship between the thread pulling technique activity and the fine motor development of early childhood group A children aged 4-5 years at the Beringin Permai Perumnas Pagar Beringin Kindergarten. The research method used is a descriptive quantitative research method. The research population was all 25 children at the Beringin Permai Perumnas Pagar Beringin Kindergarten. Data were collected using a positive closed questionnaire with 10 items for variable : 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.641 > rtable (a=0.05,n=25) = 0.396, thus it is known that there is a positive relationship between variable X and variable Y. b) Testing a significant relationship obtained a value of tcount= 4.006 > ttable(a=0.05, dk=n-2=23)= 2.069, thus there is a significant relationship between variable X and variable Y. c) Test the regression coefficient of determination (r2) = 41.1%.2) Influence test: Regression equation test, obtained the regression equation Y ̂="15","57"+0.52X. Thus, Ha is that there is a relationship between the thread pulling technique activity and the fine motor development of early childhood children in group A aged 4-5 years at the Beringin Permai Kindergarten Perumnas Pagar Beringin and H0 is rejected.